PROPAGANDA INTELEKTUAL INDISCHE PARTIJ: : STRATEGI MEDIA DAN PENDIDIKAN DALAM MEMBANGKITKAN KESADARAN NASIONAL (1912–1925) - Fahmi, Rezza Fauzi Muhammad; Septi Laila Nurpadilah; Siti Rahmawati Sudrajat; Rahil Nur Syamsi (Universitas Negeri Surabaya, 2025)
This research is entitled Intellectual Propaganda of the Indische Partij: Media and Education Strategies in Raising National Consciousness (1912-1925). Amidst colonial domination, Indische Partij faced significant challenges in fostering unity among a society fragmented by ethnic differences, social classes, and colonial political influences. This study aims to analyze Indische Partij strategies in utilizing media and education as propaganda tools to overcome these challenges and drive national consciousness. The historical method, which includes heuristics, criticism, interpretation, and historiography, was employed in the preparation of this article. Additionally, qualitative analysis and a historical approach were applied through an examination of archival documents, publications, and educational texts designed by Indische Partij . The findings reveal that media played a crucial role in widely and rapidly disseminating ideas of unity and independence, particularly through provocative articles criticizing colonial policies. On the other hand, education was used as a long-term strategy to shape national character by instilling values of justice, equality, and unity among the younger generation. These findings demonstrate that the combination of media and education as propaganda tools successfully influenced public discourse and laid the initial foundation for national awareness. Indische Partij strategies not only addressed the colonial challenges of their time but also served as an inspiration for subsequent nationalist movements in the struggle for Indonesia's independence.